Wind variability across the North Humboldt Upwelling System - Yari, Sadegh; Mohrholz, Volker; Bordbar, Mohammad Hadi (Frontiers in Marine Science, 2023)
Surface wind is taken as the primary driver of upwelling in the eastern boundary upwelling systems. The fluctuation of momentum flux associated with the variation in wind regulates the nutrient supply to the euphotic surface layer via changing the properties of oceanic mixed layer depth, the coastal and offshore upwelling, and horizontal advection. Here, the spatial and temporal variability of the surface wind field over the last seven decades across the Peruvian upwelling system is investigated. Strong fluctuations in seasonal to decadal timescales are found over the entire upwelling system. A semi-periodic wind fluctuation on an interannual timescale is found, which is closely related to the regional sea surface temperature and can be attributed to the El Niño Southern Oscillation (ENSO). However, the wind anomaly patterns during positive and negative phases of ENSO are not opposite, which suggests an asymmetric response of local wind to ENSO cycles. In addition, a semi-regular fluctuation on the decadal timescale is evident in the wind field, which can be attributed to the Interdecadal Pacific Oscillation (IPO). Our results show that the sea surface temperature over the Humboldt Upwelling System is closely connected to local wind stress and the wind stress curl. The SST wind stress co-variability seems more pronounced in the coastal upwelling cells, in which equatorward winds are very likely accompanied by robust cooling over the coastal zones. Over the past seven decades, wind speed underwent a slightly positive trend. However, the spatial pattern of the trend features considerable heterogeneity with larger values near the coastal upwelling cells.